PENDAMPINGAN PELATIHAN PEMELIHARAAN DAN REJUVINASI TANAMAN KOPI ROBUSTA DI KEBUN POLITEKNIK NEGERI JEMBER - Hatmiyarni Tri Handayani; Dian Hartatie; Ujang Setyoko (Bajang Institute, 2025)
Coffee is one of the plantation commodities that plays an important role as foreign exchange for the country. Politeknik Negeri Jember has a collection garden that includes non-productive robusta coffee plants, which can no longer be used for student practicals, research, and coffee production due to their very limited productivity. The maintenance and rejuvenation of the coffee plants have not been carried out optimally. The purpose of this activity is to provide guidance on the maintenance and rejuvenation of robusta coffee plants. The methods used in this activity are discussion and practical work. This activity enables technicians, lecturers, and students at Politeknik Negeri Jember to learn how to properly maintain and rejuvenation robusta coffee plants and to evaluate what has been done previously. The target for the implementation of this activity is 90%, indicating that it can be said that this activity has been successful.